(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Aphthous ulcers, also known as canker sores, are painful lesions that affect the oral mucosa, causing discomfort and impacting quality of life. Despite their prevalence, the exact etiology of aphthous ulcers remains unclear, though immune system dysfunction, genetic predisposition, trauma, microbial infections, and hormonal changes are implicated. This article provides a comprehensive overview of the causes, symptoms, and risk factors associated with aphthous ulcers.